EFFECT OF NET PROFIT MARGIN, PRICE TO BOOK VALUE EARNING PER SHARE ON STOCK RETURNS : in Food and Beverage Companies Listed on The Indonesia Stock Exchange - Fausyah, Nur; Musa, Muh Ichwan; Nurman; Musa, Chalid Imran; Amin, Andi Mustika (Journal Management & Economics Review (JUMPER), 2023)
The aim of this research is to determine the effect of net profit margin, price to book value, and earnings per share on stock returns in food and beverage companies listed on the IDX in 2018-2022. The independent variables in this research are net profit margin, price to book value, and earnings per share. The dependent variable in this research is stock returns.The population in this research is food and beverage companies registered on the IDX for the 2018-2022 period. The sampling method in this research is purposive sampling, namely the sampling technique uses certain criteria, 10 companies were obtained that met these criteria so that the total sample in this research was 50 samples. The analytical method used in this research is the multiple linear regression analysis method. The results of this research show that net profit margin has a negative and significant effect on stock returns in food and beverage companies listed on the IDX, while price to book value and earnings per share have a positive and significant effect on stock returns in food and beverage companies listed on the IDX , and simultaneously net profit margin, price to book value, earnings per share have a positive and significant effect on stock returns in food and beverage companies listed on the IDX.